Voltage sag signal generator program for testing electrical equipment - Jantee,W. (2015)
© 2014 IEEE. Voltage sags are the most prevalent disturbance in electrical power system. This paper presents development of waveform generator based on MATLAB graphics user interface (GUI) and the microcontroller for generated waveform. The waveform generator allows users to select sag magnitude, sag duration, phase shift and voltage sag type of the each voltage sag. The waveform generator sends the parameter of the voltage sag waveform to the microcontroller to create the voltage sag. The simulation and experimental results have shown that this prototype can be used as voltage sag waveform generator.